Evaluasi Program Kelas Industri pada Program Keahlian Teknik Otomotif SMK Negeri 2 Yogyakarta - Priti, Priti; Sofyan, Herminarto; Budiman, Agus; Sriyanto, Joko (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
The aim of this study is to describe the effectiveness of the Industrial Class program evaluation within the Automotive Engineering Skills program at SMK Negeri 2 Yogyakarta, focusing on context, input, process, and product evaluation models. Employing the CIPP model (Context, Input, Process, Product), this research follows an evaluative descriptive approach, utilizing questionnaires, interviews, documentation, and observation methods. The study involved four Industrial Class program teachers and 108 students from the Automotive Engineering program at SMK Negeri 2 Yogyakarta. Instrument validation was conducted through expert judgment, while instrument reliability was assessed using Cronbach's alpha. Both qualitative and quantitative descriptive analyses were employed for data analysis. The findings indicate areas for improvement within the Automotive Engineering Industry Class program at SMK Negeri 2 Yogyakarta. In the context evaluation, the SMK-Industry partnership revealed areas in need of enhancement. In terms of input evaluation, student interest, self-confidence, and satisfaction percentages were 35.19%, 44.44%, and 45.37% respectively, while facilities and infrastructure were deemed to meet industry standards. Regarding process evaluation, the implementation of learning and the use of learning media were rated as fairly good, with a percentage of 35.19%. However, the utilization of learning resources and assessment methods were found to be very good. In the product evaluation, student learning outcomes reached a percentage of 90% in the very good category, and graduate absorption was at a high percentage of 78%.